Acceptance Tendency of High-Level Taxis: From the Passengers’ Perspective - Rong-Chang Jou; Ke-Hong Chen (Journal of Advanced Transportation)
In the present study, we used the stated preference approach to design different situations, including appearance, different services, and different times to further explore passengers’ acceptance of and expected price to be paid for taxi service levels. In addition to using general ordered models, the results of this study were also compared with the multinomial logit model and the partial proportional odds (PPO) model. The results of comparison between the models ultimately revealed that the PPO model statistically had a better explanatory power. In the model estimation results, the key explanatory variables included the ability to recognize the appearance, seating space, honorable service, the development of user payment concepts, and demographic grouping, all of which could increase acceptance. The results obtained in this study could provide a key reference for the classification of taxis in the Taiwan region and serve as a basis for the development of strategies by operators in the future.